Stock Price Regression Model Based On Current Ratio, Earnings Per Share, Price Book Value, And Total Asset Turnover Of Properties And Real Estate Companies For The 2020-2022 Period - Nurjanah, Putri Rizki; Tohari, Amin; Nurdiwaty, Diah (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research Objectives: The purpose of this study is to determine the partial and simultaneous influence of the Current Ratio, Earning Per Share, Price Book Value and Total Asset Turnover variables on share prices in Property and Real Estate companies listed on the IDX for the 2020-2022 period. Research Method: This research uses quantitative research methods. The data used in this research is secondary data in the form of financial reports of Properties and Real Estate companies listed on the IDX for the 2020-2022 period. The sampling technique used was a purposive sampling technique with samples obtained from 21 companies. The data analysis techniques used are classical assumption testing, multiple linear regression and hypothesis testing using SPSS 23 software. Research Findings: The results of this research show that partially Earning Per Share and Price Book Value have a significant effect on Stock Prices, while the Current Ratio and Total Asset Turnover do not have a significant effect on Stock Prices. Simultaneously Current Ratio, Earning Per Share, Price Book Value, and Total Asset Turnover together have a significant effect on Share Prices. Keywords: Current Ratio, Earning Per Share, Price Book Value, Total Asset Turnover, Stock Price